Implementasi Culturally Responsive Teaching pada Materi Calistung Bilangan sampai 100 Kelas II SD Kanisius Wates - muhammad, sholeh malik (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to analyze how the implementation of the Culturally Responsive Teaching approach in reading, writing and counting numbers up to 100 in grade 2 of Kanisius Wates Elementary School. This research uses a qualitative data analysis method. Data collection techniques were carried out using observation and reflection journals. The research stage begins with observing the characteristics and background of students. After observing the characteristics and background of students then compiling learning modules, conducting learning, evaluation and reflection. The results of the reflection become material that will be used as evaluation to obtain important points related to learning process. The results of the evaluation will show the effectiveness of implementing the use of Culturally Responsive Teaching in learning activities. The result obtained is that the Culturally Responsive Teaching approach is effectively applied in learning. This is evidenced by a good percentage of effectiveness, namely that there are 29% of students who get a score of 100, 17% of students get a score of 95, 7% of students get a score of 90, 31% of students get a score of 85, 13% of students get a score of 80, and 3% of students get a score of 75. By With the learning results obtained, it can be seen that the Culturally Responsive Teaching approach is effectively applied in learning.